Authorship trends in the Journal of Orthopaedic Research: A bibliometric analysis. Issue 11 (13th June 2018) - Seetharam, Abhijit; Ali, Mohammed T.; Wang, Christine Y.; Schultz, Katherine E.; Fischer, James P.; Lunsford, Shatoria; Whipple, Elizabeth C.; Loder, Randall T.; Kacena, Melissa A.
ABSTRACT: Publications are an important tool to measure one's success and achievement in academia. They can help propel a career forward and move one into a position of leadership. The overall purpose of this study was to investigate changes in bibliometric variables, authorship, and collaboration trends in the Journal of Orthopaedic Research ( JOR ®), since its inception in 1983. A bibliometric analysis was completed for all manuscripts meeting the inclusion criteria (638), which were published throughout the inaugural year plus one representative year of each decade. Several parameters were investigated including numbers of manuscripts, authors, collaborating institutions/countries, references, pages, and citations; region of origin and gender of authors over time and by region were main focuses. Significant increases over time were observed in all bibliometric variables analyzed except in the number of pages and citations. There was an approximate 27% point increase for both female first and corresponding authors from 1983 to 2015. While this is most likely due to the increase in the number of women that have entered the field over time, similar increases in the percentage of women holding positions on the JOR editorial board or in leadership positions within in the field may have also contributed to improvements in gender parity. Understanding changes in publishing characteristics over time, by region, and by gender are critical, especially with the rising demands of publishing in academia. JOR has seen increase in most variables analyzed, including improvements in authorship by women in the field of orthopaedic research. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:3071–3080, 2018.